Assessment and Care of the Well Newborn - Thureen, Patti J (Elsevier, 2005)
Offering a multidisciplinary approach in an accessible outline format, this practical handbook covers all aspects of care for the full-term, well newborn. Written and reviewed by both physicians and nurses, this new edition presents explanations of the events surrounding delivery, the processes necessary to identify newborns that deviate from the norm, the immediate interventions and care required in these situations, and routine care considerations frequently encountered in caring for these infants. Detailed guidance is provided on assessment, delivery room management, transition and post-transition care, and commonly seen problems. Readers will also find information on the assessment of infections, nursery protocols, standardized physician standing orders, and common drugs and their effect on breastfeeding.